Adenosquamous carcinoma of the endometrium. Issue 11 (November 1976) - Haqqani, M T; Fox, H
Abstract : An adenosquamous carcinoma of the endometrium is one which contains both malignant glandular and malignant squamous components; such tumours are considered rare in Britain but are thought to account for nearly one-third of all endometrial neoplasms in the United States. A survey of 675 cases of endometrial cancer seen during the period 1956-75 showed that the incidence of adenosquamous carcinoma was 5%, an incidence that remained static during this 20-year period. The principal difficulties encountered in the diagnosis of these neoplasms are in identifying the squamous component as such and in differentiating it from benign metaplastic squamous epithelium. The prognosis for patients with an endometrial adenosquamous carcinoma is very much worse than for women with a pure adenocarcinoma, and because these neoplasms are often wrongly identified it is possible that the currently accepted prognoses for both pure adenocarcinoma and adenoacanthoma of the endometrium may have to be revised. There appears to be a true variation in the incidence of this neoplasm between Britain and the United States.